Muscle Architecture of Leg Muscles: Functional and Clinical Significance - Gurpreet Kaur; Rekha Lalwani; Manal M. Khan; Sunita A Athavale (Acta Medica Lituanica)
Background. Architectural properties of the muscles are the prime predictors of functional attributes and force-generating capacity of the muscles. This data is vital for musculoskeletal modelling and selecting the appropriate muscle–tendon units for tendon transfers. Cadaveric data for architectural properties is the gold standard and primary input for musculoskeletal modelling. There is a paucity of these datasets, especially in the leg muscles. Methods. Sixty muscles of the anterior and lateral compartments from twelve formalin-fixed lower limbs were studied for gross architecture, including the peculiar fibre arrangements and architectural properties of muscles. Muscle weight, muscle length, fibre length, pennation angle and sarcomere length were measured. Normalised fibre length, fibre length to muscle length ratio (FL/ML ratio), and the physiological cross-sectional area (PCSA) were calculated from the obtained data. Results. Muscles displayed a combination of architectural strategies and were partly fusiform and partly pennate. The tibialis anterior and peroneus longus were the heaviest muscles in their respective compartments and showed more extensive origin from the nearby deep facial sheets. Long fibre length and less pennation angle were seen in muscles of the extensor compartment. Potential muscle power was highest in the tibialis anterior and peroneus longus and least in the extensor hallucis longus. Conclusions. Arching of the foot and eversion are peculiar to humans and recent in evolution. Due to the functional demand of maintaining the medial longitudinal arch and eversion, the tibialis anterior and peroneus longus have more muscle weight and larger physiological cross-sectional area and are potentially more powerful. Extensor compartment muscles were architecturally more suited for excursions because of the long fibre length and less pennation angle. This study contributes baseline normative data for musculoskeletal modelling platforms and simulation tools – an emerging area in biomechanics and tendon transfers.